2018
DOI: 10.24107/ijeas.447650
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Structural Analysis of First Stage Gas Turbine Rotor Blade Materials for Optimum Service Performance

Abstract: During gas turbine operation, the vibration that occurs at high speed, hot gases entering the combustion chamber and other operational factors affect the longevity of gas turbine blade. This paper is focused on the selection of suitable materials that can withstand the severe working condition and thermo-structural analysis using Finite Element method (FEM) to determine the behaviour of each material under service condition. Cambridge Engineering Software (CES) was employed in the material selection process wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…According to Ikpe et al [14], Von-mises stress criterion helps in predicting the yield point of a material when subjected to complex loading conditions. The Von-mises failure theory states that a given material under the influence of forces is prone to failure if the Von mises stress resulting from the reaction forces exceed the material yield strength, but if the Von-mises stress value is less than the material's yield strength, such material still has the capacity to accommodate additional forces [15]. This relates to the theory behind elasticity of materials which states that the material can take additional load provided its elastic limit is not exceeded [16].…”
Section: Resultsmentioning
confidence: 99%
“…According to Ikpe et al [14], Von-mises stress criterion helps in predicting the yield point of a material when subjected to complex loading conditions. The Von-mises failure theory states that a given material under the influence of forces is prone to failure if the Von mises stress resulting from the reaction forces exceed the material yield strength, but if the Von-mises stress value is less than the material's yield strength, such material still has the capacity to accommodate additional forces [15]. This relates to the theory behind elasticity of materials which states that the material can take additional load provided its elastic limit is not exceeded [16].…”
Section: Resultsmentioning
confidence: 99%
“…In the field of turbine fault diagnosis, the commonly used diagnostic strategies are comparative diagnosis, logical diagnosis, statistical diagnosis, pattern recognition, diagnosis based on gray theory, fuzzy diagnosis, expert systems, and diagnosis based on artificial neural networks. Bailey established a Bayesian network model, which is mainly used to deal with the damage mechanism of the dynamic blades of turbines and the interaction of failure modes [15]. The experimental results showed that the cracks were closed in the case of the compression part expansion rate of the fatigue cycle.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, royal blue which is at the bottom of the color band indicates safe zones as well as the areas with minimum stress concertation on the wheel component. Sky blue indicates the stress level at which the shaft material begins to respond to the applied load, aqua (SVG) blue indicates further stress level from sky blue color [36,37]. Figure 7 shows the maximum Von-mises stress derived from each of the auto wheel material employed in this study.Results shown on the plot in Figure 7 reveals that carbon fibre (T300) had the highest static nodal stress (5.35E+04 N/m^2), followed by magnesium alloy (4.22E+04 N/m^2), 2014-T6 aluminium alloy (3.14E+04 N/m^2 and then cast alloy steel as the least (1.14E+04 N/m^2).…”
Section: Magnesium Alloymentioning
confidence: 99%
“…The centre of the wheel is bored of a circular hole were an axle bearing is tightened about to enable the wheel rotate when a moment generated by the auto engine is applied to the vehicle axle about its axis and the wheel [1]. In other words, the wheel is one of the most important rotating circular member of a vehicle, upon which the tyre is installed in between the flange at a pressure (35)(36)(37)(38)(39)(40) different from the ambient pressure [2,3]. Automobile wheel assembly is one of the most important aspects that determine mobility in automotive applications and its failure can be hazardous if not properly engineered to bring out the best performance, strength, durability and reliability.…”
Section: Introductionmentioning
confidence: 99%